Identifikasi Tipologi Ruang Terbuka Publik Perkotaan Taman Catur Ayani Kota Pontianak, Kalimantan Barat - Wulandari, Agustiah (Jurnal Arsitektur Lansekap, 2022)
Identification of Typology of Urban Public Open Space Taman Catur Ayani, Pontianak City, West Kalimantan . Open space is the embodiment of urban environmental development. The arrangement of public open spaces affects affecting people in urban areas. Public Open space is a place of recreation and infrastructure for community interaction in urban areas. Taman Catur Ayani is located in Kota Pontianak, Kalimantan Barat Province. This study aims to identify the typology of Non-Green Open Space in Taman Catur Ayani, Kota Pontianak. The research method used is qualitative. It collects data using direct observation of visitors' activities to Taman Catur Ayani. Based on the study results, This park has 5 (five) typological characteristics in Non-Green Open Spaces, namely: plazas, parking lots, sports fields, playgrounds and recreation areas, barriers, and corridors. The dominant activity in Taman Catur Ayani is architectural typology. The function of public space that does not yet exist in this park is incidental. Because it is an open space in the city center, this park cannot accommodate any emergency activities.